2014
DOI: 10.1589/jpts.26.93
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combination Patterns of Proprioceptive Neuromuscular Facilitation and Ball Exercise on Pain and Muscle Activity of Chronic Low Back Pain Patients

Abstract: [Purpose] The purpose of this study was to compare two methods for the muscle stabilization of the trunk of patients with chronic low back pain. The methods comprised combination patterns of proprioceptive neuromuscular facilitation (PNF) and ball exercise. [Subjects and Methods] The subjects were 40 volunteers who had low back pain. All subjects were randomly assigned to either a group which received proprioceptive neuromuscular facilitation or a group which performed ball exercise. Measurements were taken fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 13 publications
0
42
0
1
Order By: Relevance
“…Pain was rated on a scale of 0-10, in which 0 correspond to no pain, while 10 correspond to the severest pain which the participant could not stand. 19 The ODI was used to evaluate the functional status of participants, i.e. the influence of NSLBP on daily function.…”
Section: Outcomes Assessmentmentioning
confidence: 99%
“…Pain was rated on a scale of 0-10, in which 0 correspond to no pain, while 10 correspond to the severest pain which the participant could not stand. 19 The ODI was used to evaluate the functional status of participants, i.e. the influence of NSLBP on daily function.…”
Section: Outcomes Assessmentmentioning
confidence: 99%
“…Exercise interventions, aimed at facilitating abdominal and back muscle performance and enhancing proprioception, could improve clinical outcomes in CLBP patients (George et al, 2013;Kofotolis & Kellis, 2006;Kofotolis et al, 2008;Lee et al, 2014). Proprioceptive neuromuscular facilitation (PNF) training is widely used by physical therapists to treat CLBP patients (George et al, 2013;Kofotolis & Kellis, 2006;Kofotolis et al, 2008;Lee et al, 2014) in order to promote or augment neuromuscular responses by stimulating proprioceptors (Adler et al, 2014). The PNF patterns are spiral and diagonal directions which are accordance with topographic arrangement of the muscle being used in activities and sports (Adler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several PNF training techniques have been proposed for CLBP patient applications (George et al, 2013;Kofotolis & Kellis, 2006;Kofotolis et al, 2008;Lee et al, 2014;Voight et al, 2008). Three commonly used techniques are rhythmic stabilization (RS), a combination of isotonics (COI) and "chop and lift" (CL) (George et al, 2013;Kofotolis & Kellis, 2006;Kofotolis et al, 2008;Lee et al, 2014;Voight et al, 2008).The RS technique is primarily used for managing conditions where muscle weakness is a major factor, and where stabilization can stimulate the agonist movement pattern (Adler et al, 2014). The COI technique is used to improve the ability to perform controlled movements, and to address deficiencies in strength and range of movement (Adler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, in comparing modalities of exercises therapy, PNF was shown to have better result than manual therapy, core stability exercise and ball exercise for LBP and commonly used for the trunk muscle, pelvic stability, and core muscle 13,14,15,16 . 13,14,15,16,18,19,20 .…”
mentioning
confidence: 93%